Ileal volvulus secondary to postsurgical adhesion syndrome. A case report - Paolo Martini; Jorge Luis Estepa Pérez; Annalisa Noemi Garrini; Biagio Di Trani (Medisur)
Small intestine volvulus consists of an abnormal torsion, around the axis or its own mesentery. It produces a mechanical obstruction of the intestine. It may also be accompanied by torsion and occlusion of the mesenteric vessels, leading to intestinal ischemia and finally necrosis. This entity is rare in adults, it represents only 0.5 - 2.5% of intestinal obstruction cases, for this reason the case of a patient who went to the hospital due to abdominal pain and vomiting, in regular cases, sore fascie, feverish, dehydrated , is presented conditions. Upon examination, a distended abdomen was evident, with air-fluid sounds present of good tone and frequency, painful on palpation, and increased abdominal tympany. It was decided to enter for clinical management and diagnostic support studies. The surgical intervention was performed when his state of health improved, finding: great distention of thin loops, change in color of a segment of the terminal ileum, strong flange or adhesion, which caused twisting of said segment, and peritoneal fluid. Adhesion release, devolvulation, decompression and suturing were performed in two planes of deserosation, thereby achieving improvement in vascularization and intestinal motility; a toilette was performed and drainage was placed in the Douglas bag. In a patient with acute obstructive abdomen, with previous surgical intervention, a secondary complication to adhesion syndrome should be suspected.